Reversible Mechanically Induced On–Off Photoluminescence in Hybrid Metal Halides. (9th December 2021) - Fan, Liubing; Liu, Ke; He, Shihui; Zhao, Fangyi; Zhao, Jing; Wang, Yonggang; Liu, Quanlin
Abstract: Stimulus‐responsive photoluminescent materials have attracted extensive research attention in recent years owing to their potential application in information storage and switch devices. It is important to further explore such bistable materials as well as the underlying transformation mechanisms. Herein, the syntheses and mechanically tunable "on–off" photoluminescence (PL) of two organic–inorganic hybrid metal halides, (Bmpip)9 Pb3 Zn2 Br19 and (Bmpip)9 Pb3 Cd2 Br19 (Bmpip + = 1‐butyl‐1‐methyl‐piperidinium, C10 H22 N + ), are reported. Both as‐obtained compounds are nonemissive under UV light at ambient conditions but exhibit bright PL upon grinding or under hydrostatic pressure. Interestingly, the PL is quenchable by short‐time annealing or storage in air for 1 week, and the process is repeatable. Through a combination of extensive structural and spectral analyses, the crucial role of the organic cations interacting with inorganic chromophores in the "on–off" PL behavior of the title compounds is revealed. Moreover, pressure‐induced PL and PL‐enhancement phenomena are observed in both compounds, which are similar to but slightly different than the above‐mentioned mechano‐PL. Finally, proof‐of‐concept devices are fabricated to demonstrate the potential applications of the title compounds in message recording and force sensing. Abstract : Two organic–inorganic hybrid metal halides (Bmpip)9 Pb3 Zn2 Br19 and (Bmpip)9 Pb3 Cd2 Br19 with stimulus‐responsive reversible photoluminescent "on–off" properties have been discovered, and the mechanism of stimulus‐responsive properties have been studied by high‐pressure and spectral experiments. A composite film has been fabricated by combing (Bmpip)9 Pb3 Cd2 Br19 and polydimethylsiloxane to exhibit potential applications of title compounds in sensing and detection.